Can knowledge be created and shared on the move? The case of collaborative problem-solving in the mobile workers’ context - Francisco, Rosemary (2017)
Mobile workers are professionals who frequently work on the move, far from a fixed workplace, often performing knowledge-intensive activities. Mobility brings challenges to the processes of knowledge creation and sharing of these workers, and the existing literature lacks theoretical frameworks to explain these phenomena. Considering this gap, this study seeks to answer the following research question: How knowledge creation and knowledge sharing are carried out in collaborative problem-solving situations in the mobile workers’ context? The primary purpose of this investigation is to analyse how knowledge creation and knowledge sharing are carried out in collaborative problem-solving situations in the mobile workers’ context. To reach the research goals, this study applied Activity Theory (AT) and its key concepts as a theoretical lens. This theoretical approach allowed better understanding both the individual (the mobile worker) as well as his relations in his/her social context. Besides, the adoption of the Design Science Research method (DSR) provided tools for a deeper understanding of the research problem and also to propose an approach to stimulate knowledge creation and sharing through collaborative problem-solving in the mobile workers’ context. The results of this study helped to understand the fundamental needs of mobile workers related to knowledge creation and knowledge sharing to solve work problems. It was observed that these workers use their ICT tools, especially mobile ICT, to conduct the majority of their collaborative problem-solving situations and subsequently, to create and share knowledge on the move. The findings also highlight how mobile technologies are used to support collaborative problem-solving in the mobile work’ context. Therefore, the key argument tested and supported in this thesis is that collaborative problem-solving mediated by mobile ICT can support and stimulate knowledge creation and knowledge sharing in the context of mobile workers. This research makes a theoretical contribution by exploring this key argument with the use of AT as a theoretical lens. Since this theory was not used so far to analyse practices of knowledge creation and sharing in the context of mobile workers, this study contributes to the expansion of this theory in this subject. The results of the empirical data also provided lessons from the practice that can contribute to the theory, mainly considering the diversity of workplaces that mobile workers can use to perform their work activity. Also, this study provides methodological and practical contributions; through a detailed descriptive of how to apply the DSR in IS (Information Systems) studies, in addition to the artifact developed that can be used in practice. Finally, this study addresses some questions that can be explored in future research.